Enhancing Industrial Sustainability in Uzbekistan through Solar Energy Adoption in Reducing Costs and Carbon Emissions - Ivanov, Aleksandr Sergeyevich; Tursunov, Muhammadali Ikboljon; Akbarov, Mustafo; Rahimova, Soliha; Sharipov, Mirzo-Ulugbek; Abdullaev, Kamiljan (Journal of Engineering, Technology, and Applied Science (JETAS), 2024)
This study evaluates the impact of solar energy adoption on industrial sustainability in Uzbekistan, focusing on both economic and environmental outcomes. A mixed-methods approach was employed, combining quantitative data from energy savings, carbon emissions reduction, and operational cost savings with qualitative analysis from interviews and field observations across three villages: Mirzo-Ulugbek, Karakol, and Fergana. The results indicate that higher adoption of solar energy, particularly in Mirzo-Ulugbek, led to significant improvements, including a 30% reduction in energy use, a 40% decrease in carbon emissions, and a 25% saving in operational costs. In contrast, Karakol, with minimal solar adoption, showed much lower reductions. The study also highlights the challenges of widespread adoption, such as high initial investment, technological limitations in integrating solar systems, and regulatory obstacles. Data were analyzed using comparative analysis, with a focus on identifying the barriers and benefits specific to Uzbekistan’s industrial context. The findings suggest that while solar energy offers substantial potential for economic and environmental sustainability, overcoming financial and infrastructural challenges is essential for its broader adoption. Future research should explore financing models, policy development, and international case studies to further facilitate solar integration into Uzbekistan’s industrial sectors